Uji Aktivitas Antiinflamasi Ekstrak Etanol Daun Talas (Colocasia esculenta) Terhadap Mencit Putih Jantan (Mus musculus) - Nur Dania, Sharifah; Rachmayanti, Aprilya Sri; Suhailah, Dhia (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Inflammation is a physiological response to tissue injury, infection, or harmful stimuli, characterized by redness, swelling, heat, and pain. However, excessive or chronic inflammation may lead to tissue damage and degenerative diseases. Long-term use of non-steroidal anti-inflammatory drugs is associated with gastrointestinal and cardiovascular side effects, highlighting the need for safer natural alternatives. Taro leaves (Colocasia esculenta) are traditionally used to treat swelling and wounds and contain bioactive compounds such as flavonoids, alkaloids, tannins, saponins, and triterpenoids with potential anti-inflammatory effects. This study aimed to evaluate the anti-inflammatory activity of ethanol extract of taro leaves and determine the most effective dose. An experimental study was conducted using male white mice (Mus musculus) divided into five groups: negative control (Na-CMC), positive control (sodium diclofenac), and three treatment groups receiving extract doses of 25, 50, and 75 mg/kg BW. Inflammation was induced by 1% carrageenan injection. The extract significantly reduced inflammation, with the highest inhibition (84.13%) observed at 75 mg/kg BW, comparable to diclofenac.